Disease- and Treatment-related Morbidity in Adolescents With Perinatal HIV Infection in Asia. Issue 3 (March 2019) - Bartlett, Adam W.; Mohamed, Thahira Jamal; Sudjaritruk, Tavitiya; Kurniati, Nia; Nallusamy, Revathy; Hansudewechakul, Rawiwan; Ly, Penh Sun; Truong, Khanh Huu; Lumbiganon, Pagakrong; Puthanakit, Thanyawee; Chokephaibulkit, Kulkanya; Nguyen, Lam Van; et al.
Abstract : Background: Perinatally HIV-infected adolescents (PHIVA) are exposed to a chronic systemic infection and long-term antiretroviral therapy (ART), leaving them susceptible to morbidities associated with inflammation, immunodeficiency and drug toxicity. Methods: Data collected 2001 to 2016 from PHIVA 10–19 years of age within a regional Asian cohort were analyzed using competing risk time-to-event and Poisson regression analyses to describe the nature and incidence of morbidity events and hospitalizations and identify factors associated with disease-related, treatment-related and overall morbidity. Morbidity was defined according to World Health Organization clinical staging criteria and U.S. National Institutes of Health Division of AIDS criteria. Results: A total 3, 448 PHIVA contributed 17, 778 person-years. Median age at HIV diagnosis was 5.5 years, and ART initiation was 6.9 years. There were 2, 562 morbidity events and 307 hospitalizations. Cumulative incidence for any morbidity was 51.7%, and hospitalization was 10.0%. Early adolescence was dominated by disease-related infectious morbidity, with a trend toward noninfectious and treatment-related morbidity in later adolescence. Higher overall morbidity rates were associated with a CD4 count <350 cells/µL, HIV viral load ≥10, 000 copies/mL and experiencing prior morbidity at age <10 years. Lower overall morbidity rates were found for those 15–19 years of age compared with 10–14 years and those who initiated ART at age 5–9 years compared with <5 or ≥10 years. Conclusions: Half of our PHIVA cohort experienced a morbidity event, with a trend from disease-related infectious events to treatment-related and noninfectious events as PHIVA age. ART initiation to prevent immune system damage, optimize virologic control and minimize childhood morbidity are key to limiting adolescent morbidity. Abstract : Supplemental Digital Content is available in the text.